Perforated small intestine in a patient with T-cell lymphoma; a rare cause of peritonitis - Petrişor Banu; Vlad D. Constantin; Florian Popa; Mihaela F. Nistor (Journal of Mind and Medical Sciences)
The nontraumatic perforations of the small intestine are pathological entities with particular aspects in respect to diagnosis and treatment. These peculiarities derive from the nonspecific clinical expression of the peritonitis syndrome, and from the multitude of causes that might be the primary sources of the perforation: foreign bodies, inflammatory diseases, tumors, infectious diseases, etc. Accordingly, in most cases intestinal perforation is discovered only by laparotomy and the definitive diagnosis is available only after histopathologic examination. Small bowel malignancies are rare; among them, lymphomas rank third in frequency, being mostly B-cell non Hodgkin lymphomas. Only 10% of non-Hodgkin lymphomas are with T-cell. We report the case of a 57 years’ old woman with intestinal T-cell lymphoma, whose first clinical symptomatology was related to a complication represented by perforation of the small intestine. Laparotomy performed in emergency identified an ulcerative lesion with perforation in the jejunum, which required segmental enterectomy with anastomosis. The nonspecific clinical manifestations of intestinal lymphomas make from diagnosis a difficult procedure. Due to the fact that surgery does not have a definite place in the treatment of the small intestinal lymphomas (for cases complicated with perforation), and beyond the morbidity associated with the surgery performed in emergency conditions, prognosis of these patients is finally given by the possibility to control the systemic disease through adjuvant therapy.